INFLUENCE OF THE PRELIMINARY PREPARATION OF THE SUBSTRATES’ SURFACE ON THE MORPHOLOGY OF TWO-COMPONENT COATINGS RECEIVED IN THE INVERSE MAGNETRONIC SPRAYER SYSTEM - Денис Витальевич Слюсарь; Владимир Петрович Колесник; Олег Николаевич Чугай; Леонид Васильевич Литовченко; Евгений Иванович Ищенко; Сергей Владимирович Олейник (Авіаційно-космічна техніка та технологія, 2019)
The factors affecting the efficiency of ion cleaning of CuAl9Fe4 bronze substrates and 12X18H9T stainless steel applying the «Вихрь-К» pilot plant were investigated. The unit is equipped with an inverse magnetron sputtering system with a gas anode, partitioned by cathode assemblies and ensures the creation of radial plasma flows. It was investigated the composition and morphology of the substrates’ surface and the WC-type coatings formed on them, applying «СЭМ 106» scanning electron microscope. It has been established that the effectiveness of the ionic cleaning of the substrate surface is influenced by the magnitude of the potential, under which the target cathodes are in relation to the installation case. Under conditions of relatively high positive potential, purification does not occur at all. At the same time, at a low potential, the sputtering of the material of target cathodes is observed. Therefore, it became necessary to experimentally establish the mode of ion cleaning of CuAl9Fe4 bronze substrates and 12X18H9T stainless steel using an inverse magnetron sputtering system with a gas anode, partitioned cathode nodes, and radial plasma flows, ensuring high-quality cleaning of the surfaces of the substrates without spraying the cathodes. The mode is determined by the electrical resistance of the resistors, which are connected to the cathode nodes. The morphology and surface composition of various parts of the bronze and steel substrates, both after their ionic cleaning and with the deposited coating such as tungsten carbide, was investigated. It was established that, in contrast to coatings formed using this system with axial plasma flows, when using radial flows, there is no dependence of the surface morphology on the remoteness of the investigated coating area relative to the substrate edge. This may be due to the characteristics of the electric field and plasma flows in the vicinity of both target cathodes and metal substrates. Thus, when forming coatings of the WC type on metal substrates with the help of magnetron sputtering systems, there are certain advantages of applying radial plasma flows compared to axial flows.